(3GdOhQI GdeMGSHjIs - (3eMeO YWjI(B, (3eWQs ((3YeGf(B:s (3OGQ hGFd ddfTQ hGdJhRjY(B,s, 2007)
(3deMI Yf GdeMGSHI hfTCJgG, GdEWGQ GdeaGgjej Ch GdfXQj ddeMGSHI, GdebheGJ GdCSGSjI ddfXGe GdeMGSHj, fXGe GdbjO GdeROhL, GdOhQI GdeMGSHjI ddYedjGJ GdeGdjI, GdfXe GdeMGSHjI PGJ GdOaGJQ GdeJYOOI, eaghe GdbjeI GdMGdjI ddJOab GdfbOj GdeSJbHdj hJWHjbGJg GdYedjI, GdJShjGJ GdLQOjI, GdeMGSHI Yf GdEjQGOGJ hGdeUQhaGJs
(3HHdjhZQGajG(B: (3U(B.377(3; edGMb U(B.355s
Keywords: (3GdEOGQI GdeGdjIs; (3GdeMGSHIs; (3GdeMGSHI (B-(3GdeGdjIs